Legal Status of Firms – Main Contributors to Romanian Public Budget - Mihaela Tofan (CES Working Papers, 2014)
Public expenditure and collection of public resources generate interactions among different subjects of law, natural and legal persons, subjects of public law and private law. These interactions are the main object of the financial regulation, both at domestic and EU level. The legal relations are part of social relations and the companies legally formed are subject to the execution of the financial and fiscal liabilities, which is ensured by the state authority. Financial legal relations are distinguished from other legal relationships by the specific connection that occurs between the contributors and the state authority representative. The subjects involved and the position they have towards each other is subject to regulatory act and, if needed, court of law determination and control. In legal theory, the time of crises determine deep mutation in the legislation in force and the papers shows some of these changes and conclude on some aspects to be improved.
Keywords: K22; K34; 330; firm; legal status; Romanian law